2001
DOI: 10.1034/j.1399-3054.2001.1110108.x
|View full text |Cite
|
Sign up to set email alerts
|

Cold resistance in Antarctic angiosperms

Abstract: Deschampsia antarctica Desv. (Poaceae) and Colobanthus quitensis (Kunth) Bartl. (Cariophyllaceae) are the only two vascular plants that have colonized the Maritime Antarctic. The primary purpose of the present work was to determine cold resistance mechanisms in these two Antarctic plants. This was achieved by comparing thermal properties of leaves and the lethal freezing temperature to 50% of the tissue (LT50). The grass D. antarctica was able to tolerate freezing to a lower temperature than C. quitensis. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
101
0
8

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(121 citation statements)
references
References 72 publications
(103 reference statements)
12
101
0
8
Order By: Relevance
“…Starch content in tissues of C. quitensis was relatively low, still it was twice as high as reported by Bravo et al (2001) and comparable to the level found in A. reptans (Bachman et al 1994). Microscopic analyses have shown that it was localized in chloroplasts only.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…Starch content in tissues of C. quitensis was relatively low, still it was twice as high as reported by Bravo et al (2001) and comparable to the level found in A. reptans (Bachman et al 1994). Microscopic analyses have shown that it was localized in chloroplasts only.…”
Section: Discussionsupporting
confidence: 62%
“…It is possibly another way of setting up a carbon (assimilate) reserve, which will be used in autumn for cellular structures reconstruction, and synthesis of cryoprotectants. The level of starch in tissues of Deschampsia antarctica is very high, several fold higher than might be inferred from studies by Bravo et al (2001), carried out under unnatural conditions. These data are corroborated by microphotographs, in which many chloroplasts can be seen, containing globular, typically shaped and coloured starch grains.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…The accumulation of the above SCs could be a mechanism which conditions plant resistance to cold stress (Bravo et al 2001;Krasensky and Jonak 2012). In our study, all of the analyzed plant species responded to chilling by accumulating sucrose (Figs.…”
Section: Discussionmentioning
confidence: 89%
“…Although C. quitensis and D. antarctica were intensively analyzed to− wards their morphological, anatomical and physiological adaptations to local cli− matic conditions (e.g. Bravo et al 2001;Bravo and Griffith 2005;Giełwanowska et al 2008;Ruhland and Krna 2010), we still have limited knowledge about the genetic variability of these species. Our knowledge concerning the genetic diver− sity of these plants is based mainly on a small number of publications devoted to D. antarctica (e.g.…”
Section: Introductionmentioning
confidence: 99%